Intravascular ultrasound of the elastic pulmonary arteries: a new approach for the evaluation of primary pulmonary hypertension. Issue 3 (1st March 2003) - Rodés-Cabau, J; Domingo, E; Román, A; Majó, J; Lara, B; Padilla, F; Anívarro, I; Angel, J; Tardif, J C; Soler-Soler, J
Abstract : Objective: To assess the structural and functional characteristics of pulmonary arteries by intravascular ultrasound (IVUS) in the setting of primary pulmonary hypertension, and to correlate the ultrasound findings with haemodynamic variables and mortality at follow up. Design: Prospective observational study. Setting: University hospital (tertiary referral centre). Patients: 20 consecutive patients with primary pulmonary hypertension (16 female; mean (SD) age, 39 (14) years). Methods: Cardiac catheterisation and simultaneous IVUS of pulmonary artery branches at baseline and after infusion of epoprostenol. Results: 33 pulmonary arteries with a mean diameter of 3.91 (0.80) mm were imaged, and wall thickening was observed in all cases, 64% being eccentric. Mean wall thickness was 0.37 (0.13) mm, percentage wall area 31.0 (9.3)%, pulsatility 14.6 (4.8)%, and pulmonary/elastic strain index 449 (174) mm Hg. No correlation was observed between IVUS findings and haemodynamic variables. Epoprostenol infusion increased pulsatility by 53% and decreased the pulmonary/elastic strain index by 41% (p = 0.0001), irrespective of haemodynamic changes. At 18 (12) months follow up, nine patients had died. A reduced pulsatility and an increased pulmonary/elastic strain index were associated with increased mortality at follow up (12.0 (4.4)% v 16.4 (4.4)%, p = 0.03; 369 (67) v 546 (216) mm Hg, p = 0.02). Conclusions: IVUS demonstrated pulmonary artery wall abnormalities in all patients with primary pulmonary hypertension, mostly eccentric. The severity of the changes did not correlate with haemodynamic variables, and epoprostenol improved pulmonary vessel stiffness. There was an association between impaired pulmonary artery functional state as determined by IVUS and mortality at follow up.